THE ULTRAMAFIC-MAFIC SECTION OF THE SOUTHERN BLOCK OF THE VOLKOV PLUTON (CENTRAL URALS): NEW DATA ON THE COMPOSITION OF AU-PD MINERALIZATION - Anikina E.V.; Rusin I.A.; Pushkarev E.V.; Knauf V.V.; Garuti G.; Zaccarini F.; Bersenev S.Ya. (My University, 2004)
The Au-Pd mineralization in olivine gabbros of the southern concentric block of the Volkov Pluton is controlled by inhomogeneous taxitic clinopyroxenite, wehrlite, and olivinite zones that, probably, formed in the presence of fluid under nonstationary dynamic conditions. Appreciable mineralogical distinctions of noble metals mineralization in various rocks, on the one hand and similar concentrations and proportions of noble metals, on the other hand, indicate local variations in the crystallization condition of noble metals minerals because of fluid-matrix interaction during subsolidus cooling of the host rocks.